Continuous monitoring of sterility: Bacterial contamination and disinfectant performance in dental clinics - Tarek ABOU AGWA; Shuaib ALAHMAD; Nermin ALMOUHAMMAD; Nathaly ALSALLOUM (International Arab Journal of Dentistry (IAJD), 2025)
Objectives: This study aimed to (1) evaluate contamination levels across three clinics (endodontic, extraction and surgery, and fixed prosthodontics), (2) identify the types and prevalence of bacteria, (3) estimate the effectiveness of a commercial disinfectant, and (4) determine the bacterial species most responsive to the disinfectant.Methods: Equal surfaces (17.98 cm²) were swabbed, cultured on nutrient agar for the total aerobic microbial count before and after disinfection, and analyzed using settle plates. Bacterial identification was conducted through colony characteristics, Gram staining, and biochemical tests. Data were processed using SPSS version 26.Results: The endodontic clinic exhibited the highest contamination levels, with buttons significantly more contaminated than handles. The disinfectant effectively reduced contamination but did not eliminate it.Conclusions: Contamination levels varied significantly between the clinics; ongoing evaluation is essential.